(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
The aim of the study was to establish whether poverty (multidimensional and extreme) has increased or decreased in Mexico over the last fifteen years, as well as to indicate which states suffer from it and to make an international comparison, especially with Latin American countries. The essay followed the deductive method, hermeneutic paradigm, analytical approach and explanatory design. In 2022, 46.8 million Mexicans suffer from multidimensional poverty (36.3 per cent of the population), with 37.7 million in moderate poverty (29.3 per cent) and 9.1 million in extreme poverty (7.1 per cent); and 56.1 million in income poverty (43.2 per cent). From 2008 to 2022, moderate poverty and income poverty grew by 1% and 3%, respectively, while multidimensional and extreme poverty decreased by 5% and 26%, respectively. The entities with the highest multidimensional poverty are: Chiapas 67.4%; Guerrero 60.4%; Oaxaca 58.4%; Puebla 54%; Veracruz 51.7% and State of Mexico 42.9%; these six entities concentrate 24 million people with multidimensional poverty (55.6% of the total), the same entities have the highest extreme poverty (6.1 million people: 67.5% of the total). Internationally. At the international level, it ranks 70th out of 111 nations with the highest Multidimensional Poverty Index.